Mathematics Self-Efficacy and Study Habit as Predictors of Achievement of Senior Secondary School Students - Asanre, Akorede A.; Sondlo, Aviwe; Chinaka, Taurayi; Oluwadoyo, Taiwo Abiodun (Mathematics Education Journal, 2024)
This study therefore looked at Mathematics Self-Efficacy and Study Habit as Predictors of Academic Achievement of Senior Secondary School Students in Ijebu Ode Local Government Area, Ogun State, Nigeria. Three hypotheses that were examined at the 0.05 significance level served as the study's compass. Descriptive survey was used, 500 students sampled from 10 senior secondary schools in Ijebu ode using simple random sampling techniques. mathematical achievement test, study habit scale, and self-efficacy scale constitute the instruments, validated and demonstrates reliability coefficients of 0.78, 0.81 and 0.86. The results shows that self-efficacy and study habit will accurately forecast students' academic success in mathematics (F =38.328, p < 0.05 & F =35.011, p < 0.05) and jointly predict students' proficiency in mathematics (F = 49.136, p < 0.05). The conclusion derived is that both Study habits and self-efficacy are significant predictors of academic achievement of senior secondary school students in mathematics.